INACCURATE PRONUNCIATIONS OF ENGLISH VOWEL SOUNDS BY ONLINE INDONESIAN ENGLISH TEACHERS - Rosari, Maria Dewi; Ena, Ouda Teda (Universitas Swadaya Gunung Jati, 2019)
Many English learners use English Teaching Channels on YouTube as an alternative source of learning. Most of those channels were organized by Indonesian teachers. The qualities of the teaching presentations on these channels are varied. Inappropriate use of vocabulary, inaccurate grammar, and mispronunciations are often found in these channels. This research attempts to study the inaccurate pronunciations of the English teachers. The study is deemed necessary due to the fact that learners consider online English teachers as good language model and as an alternative to access English learning materials. The result of the study shows that there are nine types of English vowels that are pronounced inaccurately by the teachers. Most of them are absent in Indonesian vowel system. Cautions should be made when using English Teaching channels on YouTube and some suggestions for Indonesian English teachers are presented.